Greenhouse gases mitigation policies in the agriculture of Aragon, Spain - Mohamed Taher Kahil; José Albiac (Bio-based and Applied Economics, 2013)
Climate change is an important threat to human society. Agriculture is a source of greenhouse gases (GHG), but it also provides alternatives to confront climate change. The expansion of intensive agriculture around the world during recent decades has generated significant environmental damages from pollution emissions. The spatial distribution of emissions is important for the design of local abatement measures. This study makes an assessment of GHG emissions in an intensive agricultural area of Aragon (Spain), and then an economic optimization model is developed to analyze several GHG mitigation measures. The results indicate that adequate management of manure, emissions limits, and animal production restrictions are appropriate measures to abate pollution. Economic instruments such as input and emission taxes could be only ancillary measures to address nonpoint pollution problems. Suitable pollution abatement policies should be based on institutional instruments adapted to local conditions, and involve the cooperation of stakeholders.